Influence of mineral fertilizers on productivity and quality of wheat varieties seeds in the northern forest-steppe of the Tyumen region - A. A. Kazak; Yu. P. Loginov; D. I. Eremin (Аграрная наука Евро-Северо-Востока, 2019)
In the Siberian District, including the Tyumen region, a great contribution into production of foodgrain has been made by valuable and strong varieties of spring soft wheat Iren, Omskaya 36, Novosibirskaya 31. It should be noted that elements of cultivation technology of these varieties for seeds have been developed insufficiently. In the article, the 2016-2018 data have been analyzed according to the productivity and quality of seeds of the chosen wheat varieties in dependence to the level of mineral nutrition (for planned productivity of 4.5 and 6 t/ha). It has been established that in the conditions of the northern forest-steppe of the Tyumen region the level of mineral nutrition for productivity of 4-5 t/ha provided high quality of seeds. In the variant with NPK of 4 t/ha the yield of seeds of the general productivity was 73.0-77.8%, the mass of 1000 grains – 33.9-38.5, the protein content – 15.3-16.8%, the energy of germination – 58.0-67.3%, the laboratory viability – 94.3-96.5%. The main part of seeds (67-74%) sprouted in 5-6 seminal roots and when resowing in 2017-2018 it gave dense, strong shoots. Seeds from the chosen variant had advantage before the control without fertilizers and before variants with higher level of mineral nutrition in many quality indicators.  It has been established that germination energy of seeds closely correlated with protein content (r = 0.72…0.82) and insignificantly – with the mass of 1000 grains (r = 0.27…0.28). Between productivity and energy of germination of seeds the correlation was negative(r = -0,32…-0,40)